2018
DOI: 10.3390/jof4030096
|View full text |Cite
|
Sign up to set email alerts
|

Oryzines A & B, Maleidride Congeners from Aspergillus oryzae and Their Putative Biosynthesis

Abstract: Aspergillus oryzae is traditionally used in East Asia for the production of food and brewing. In addition, it has been developed into a suitable host for the heterologous expression of natural product biosynthetic genes and gene clusters, enabling the functional analysis of the encoded enzymes. A. oryzae shares a 99.5% genome homology with Aspergillus flavus, but their secondary metabolomes differ significantly and various compounds unique to A. oryzae have been reported. While using A. oryzae as a host for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Initial searches for BGC containing PKS and CS encoding genes, as found for the biosynthesis of related compounds such as 4 and 5, were not productive. However, search for fungal fatty acid synthase (FAS) genes co-located with CS genes, as found for example in the BGC for the oryzines, 16 rapidly identied closely related target BGC in all three organisms, which also encoded the expected oxygenase and decarboxylase catalysts ( Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial searches for BGC containing PKS and CS encoding genes, as found for the biosynthesis of related compounds such as 4 and 5, were not productive. However, search for fungal fatty acid synthase (FAS) genes co-located with CS genes, as found for example in the BGC for the oryzines, 16 rapidly identied closely related target BGC in all three organisms, which also encoded the expected oxygenase and decarboxylase catalysts ( Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Compounds such as oryzine A 25a (Fig. 10) requires only a single hydroxylation at C-5 performed by OryG (68% identity, 77% similarity), 16 while oryzine B 25b may arise from double hydroxylation and 3,4-dehydration. Piliformic acid 2 requires no hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…The genes coding for the enzymes involved in the biosynthesis of these compounds are associated in gene clusters. The genomes of A. niger , A. oryzae , and T. reesei include 78, 75, and 27 gene clusters for secondary metabolite biosynthesis, respectively (Lind et al 2015 ; Zeilinger et al 2016 ; Wasil et al 2018 ), although these numbers may vary depending on the strain and the software package used. Furthermore, each biosynthetic gene cluster may be responsible for the production of a large number of precursors, shunt products, and final products.…”
Section: Mycotoxins Are a Very Limited Group Of Fungal Secondary Metamentioning
confidence: 99%
“…Oryzines are maleidrides biosynthetically produced from acyl CoA thiolester and from oxaloacetic acid (Wasil et al 2018 ). RIB 203, the producing strain, is from sake-koji and thus represents a real A. oryzae .…”
Section: Secondary Metabolite Potentialmentioning
confidence: 99%
“…To identify the candidate cis-aconitate decarboxylase, we examined orthologous gene clusters predicted to be involved in alkylcitric acids biosynthesis. Previous reports have shown that alkylcitric acids and the similar structured maleidrides are being produced not only in A. niger but also in other filamentous fungi including Penicillium striatosporum 27,41 and A. oryzae 42 . Therefore, we used the alkylcitric acid cluster of A. niger as query to search for orthologous gene clusters in the published Aspergilli genomes.…”
Section: Analysis Of Orthologous Alkylcitric Acid Gene Clusters Reveamentioning
confidence: 99%